Perencanaan Dan Perancangan Beach Club Di Pemuteran Beach, Gerokgak, Kabupaten Buleleng - I Gede Komang Wahyu Ari Trisna; I Nyoman Warnata; I Nyoman Gede Maha Putra (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Beach Club is an association of several activities located on the beach and provides recreational and relaxation facilities such as restaurants, rooftops, bars, lounges, sunbathing areas, swimming pools, and several other supporting facilities. Beach Club is very much needed apart from being a place of recreation as well as a place to relax, it can also support the needs of tourists who after carrying out activities around Pemuteran Beach because of the very attractive tourism potential with stunning natural beauty and the existence of marine tourism that can be enjoyed by tourists. Therefore Pemuteran Beach is one of the beaches visited by many tourists in the North Bali area. Then the basic concept that will be applied later is